The enterovirus flora in normal children (Preliminary Communication) - Célis G., Eduardo (1969)
107 stool samples from normal children in tube cultures of the strain was inoculated Hela established; obtained 30 strains which corresponded, 8 type I poliovirus strains, four strains of poliovirus Type II, two type III poliovirus strains and 16 strains were not identified.